Analysis of the effect of ınnovation strategy and technological turbulence on competitive capabilities and organizational innovativeness in technology firms - Çeltekligil, Kudret; Adıgüzel, Zafer (Elsevier, 2019)
The aim of the research is to investigate and analyse how they are successful in industry firms of manifacturing sector in Turkey that is in the order of emerging countries, against rivalry in terms of both technological and innovation strategy. In the industrial sector where technological fluctuations are experienced intensively, it is important how companies make use of these fluctuations and how effective the innovative decisions that they take strategically. Hypothesis testing model for the study covered 344 white-collar employees in 19 companies located in the industrial sector operating in Turkey (engineers) has made a survey covering. In the analysis of hypothesis, sobel test was used for the analysis of regression analysis and mediation effect. When the constraints of the research were examined, only the firms in Istanbul were researched in terms of sample size. It is possible to obtain more reliable results of the study will represent the general case of the Turkey. The obtained empirical results support all hypotheses and show that technological fluctuations are perceived correctly by firms and they are fed by technological developments in the sector.
Keywords: Firm Innovation Strategy; Technological Turbulence; Combinative Competitive Capabilities; Organizational Innovativeness